Comparison of the accelerating effect of graphene oxide and graphene on anaerobic transformation of bisphenol F by Pseudomonas sp. LS. Issue 27 (6th December 2022) - Lu, Hong; Li, Jingyi; Fu, Ze; Wang, Xiaolei; Zhou, Jiti; Wang, Jing
ABSTRACT: It was found that bisphenol F (BPF) could be anaerobically transformed to 4, 4-dihydroxybenzophenone using nitrate as an electron acceptor by Pseudomonas sp. LS. However, BPF removal was a slow process under anaerobic conditions. In the present study, effects of graphene oxide (GO) and graphene on the anaerobic transformation of BPF were studied in detail. Results showed that GO (2–10 mg/L) and graphene (2–20 mg/L) could increase the anaerobic biotransformation rate of BPF. For GO-mediated system, GO was partially reduced, and then the reduced GO (rGO) as an electron mediator increased biotransformation rate of BPF. Further analysis showed that the promoting effect of 10 mg/L GO was over 1.5-fold higher compared with that of 10 mg/L graphene. BPF could be transformed using GO as an electron acceptor. GO and graphene was also used as nutrient scaffolds to promote cell growth via adsorbing proteins. Moreover, GO was a better cell growth promoter than graphene. These studies indicated that GO played more roles and exhibited a better accelerating effect on anaerobic removal of BPF compared with graphene. GRAPHICAL ABSTRACT: UF0001